Articulating a Notion of Self-as-Mediation—Grounded from Science and Art Towards the Religious - Lauren Ana Walker (Religions)
The intention of this paper is to develop an original notion of self-as-mediation, where a reimagining of the function of art as a phenomenological/epistemological praxis will be the methodological vehicle. The argument here will unfold over four moments. Firstly, I argue that through the elevation of art into a valid form of inquiry—one that engages our collective and individual being-in—a relation coupling art with science can be established. Secondly, by means of a further reflection on the linguistic aspects of the complementary domains of science and art—in part inspired by the standpoint of Carl Otto Apel—a unified transcendental–pragmatic interpretation of this art–science relationship will be determined. In the third moment, I make the argument that through a phenomenological reflection derived from the apodictic assertion of self-as-mediation, a trifold relation situating self-as-mediation is revealed as dynamically engaged in a continual exchange, or interchange, between what can be considered to be an “attitude” and a “doing”, referred to here as relation and action. Thus, the fourth moment is revealed as a weird dynamic relational movement, out of which a radical ethic may be developed. It is argued that along with an implied recasting of religious consciousness, a complementary and positive vision for humanity at this time of ecological and social tragedy may also be offered by this approach.